DAKWAH SINETRON MISTERI ILAHI â€œKABUT DOSAâ€ (Analisis Dakwah Sinetron Keagamaan Di Indosiar) - Muslih Aris Handayani (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2007)
Daâ€™wa recently can be done with various ways and media. One of them is via television, especially television cinema (sinetron). Sinetron becomes attractive program for audience because of its combination of colour design, lighting, picture configuration and sound that makes audience more pleasant. More over, sinetron tries to reveal the real life of human being. This article is to analyze the sinetron Misteri Ilahi Kabut Dosa. Which was broadcast by Indosiar in the first week of March 2007. Kabut Dosa is the sinetron containing massages of da â€™wa such as that forbidden to muslim to permitted all things blindly.